1989
DOI: 10.1590/s0102-76381989000100005
|View full text |Cite
|
Sign up to set email alerts
|

Tratamento cirúrgico da endocardite em prótese valvular cardíaca

Abstract: RBCCV 44205-76 POMERANTZEFF, P. M. A. ; PÊGO-FERNANDES, P. M.; KIOKA, Y.; CARDOSO, R. H. A.; GALUCCI, S. D. D.; MANSUR, A. ; DIAS, A. R. ; GRINBERG, M.; BITTENCOURT, D.; STOLF, N. A. G.; VERGINELLI, G.; JATENE, A. D. -Tratamento cirúrgico da endocardite em prótese valvular cardíaca.Rev. Bras. Cir. Cardíovasc., 4(1) : 43-50, 1989. RESUMO : No período de janeiro de 1983 a março de 1988, 1.512 pacientes foram submetidos a substituição valvar, no Instituto do Coração, sendo 28 (1,85%) deles por endocardite em prót… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
1

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 10 publications
2
6
1
Order By: Relevance
“…This was concordant with previous studies that have mentioned that these valves are the ones predominantly affected by the infectious process. 13,17 Mechanical and biological valves were similarly involved, which is also consistent with previous findings. 18 Our study found that the positivity rate among the blood cultures was low (18.8%).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…This was concordant with previous studies that have mentioned that these valves are the ones predominantly affected by the infectious process. 13,17 Mechanical and biological valves were similarly involved, which is also consistent with previous findings. 18 Our study found that the positivity rate among the blood cultures was low (18.8%).…”
Section: Discussionsupporting
confidence: 92%
“…The frequency of prosthetic valve endocarditis, considering total valve operations, was approximately 2%. This proportion is close to what was reported in the study by Pomerantzeff et al, 13 in which 28 patients presented prosthetic valve infective endocarditis out of a total of 1,512 valve operations (1.58%).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations